Economic Diplomacy Strategies for Agricultural Development and International Trade: An Exploratory Systematic Review - Diah Apriliani; Tom Finaldin (Universitas Pendidikan Ganesha, 2025)
This exploratory systematic review provides the first comprehensive examination of research at the intersection of economic diplomacy and agricultural development. Following PRISMA 2020 guidelines, 423 Scopus records were systematically screened, with 127 studies meeting inclusion criteria for analysis using the Mixed Methods Appraisal Tool. The review identified four distinct research clusters: agricultural trade promotion and export development (35.4%), international cooperation and diplomatic initiatives (25.2%), market access and competitiveness strategies (22.0%), and policy analysis and institutional frameworks (17.3%). Geographic analysis revealed substantial focus on developing countries (78.7%), particularly in Asia (42.5%) and Africa (31.5%), addressing a critical gap in understanding economic diplomacy applications in these contexts. Integrated multi-stakeholder approaches showed promising outcomes for enhancing agricultural trade competitiveness. However, significant methodological limitations constrain findings. The predominance of case study designs, limited experimental research, and restriction to English-language Scopus-indexed publications limit both comprehensiveness and the strength of causal inferences about intervention effectiveness. Practically, policymakers in developing countries should prioritize multi-stakeholder diplomatic frameworks integrating agricultural ministries, trade promotion agencies, and private sector actors to enhance export competitiveness. Additionally, development agencies and researchers must invest in rigorous experimental studies to build evidence-based guidelines for economic diplomacy interventions, moving beyond descriptive approaches to establish what works and under what conditions. This foundation enables future comprehensive reviews and targeted empirical investigation in this emerging interdisciplinary field.